1997
DOI: 10.1021/cm970075a
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive PEO-like Polymer Electrolytes

Abstract: Polymer electrolyte membranes comprising poly(vinylidene fluoride)−hexafluoropropene (PVdF−HFP) copolymer plasticized with a solution of LiSO3CF3, LiN(SO2CF3)2, or LiPF6 in oligomeric poly(ethylene glycol) dimethyl ethers (PEGDME, M w = 250, 400, and 500) were prepared by hot-melt-rolling or solvent-casting techniques. Since the electrolytes containing PEGDME400 and PEGDME500 are “dry” with essentially no volatile components up to 150 °C, we have dubbed them PEO-like. Their thermal stability, mechanical streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
306
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 437 publications
(316 citation statements)
references
References 15 publications
3
306
0
1
Order By: Relevance
“…36 These crystalline peaks are riding over a broad halo which is the indication of the amorphous phase present in the polymer PEO. It may also be observed that the "halo" is less prominent in pure PEO than PEO+LiPF 6 or PEO+LiPF 6 +BMIMPF 6 membranes. The intensity of these PEO peaks is found to decrease while broadening in the peaks increases with increasing amount of BMIMPF 6 in the PEO-LiPF 6 polymer electrolyte membranes.…”
Section: A X-ray Diffraction For Structural Characterizationmentioning
confidence: 98%
See 4 more Smart Citations
“…36 These crystalline peaks are riding over a broad halo which is the indication of the amorphous phase present in the polymer PEO. It may also be observed that the "halo" is less prominent in pure PEO than PEO+LiPF 6 or PEO+LiPF 6 +BMIMPF 6 membranes. The intensity of these PEO peaks is found to decrease while broadening in the peaks increases with increasing amount of BMIMPF 6 in the PEO-LiPF 6 polymer electrolyte membranes.…”
Section: A X-ray Diffraction For Structural Characterizationmentioning
confidence: 98%
“…In this method, polymer PEO and lithium salt LiPF 6 were weighed in desired ratio and dissolved in distilled methanol and stirred for 5-6 hours at 50 • C for complete dissociation of salt. Subsequently, desired amount of BMIMPF 6 was added and stirring continued until a viscous solution was obtained. This viscous solution was poured in polypropylene Petri dishes and solvent was allowed to evaporate at ambient condition.…”
Section: B Preparation Of Polymer Electrolyte Films and Characterizamentioning
confidence: 99%
See 3 more Smart Citations